PELAKSANAAN PROGRAM PENGEMBANGAN DIRI SISWA DI SEKOLAH MENENGAH ATAS NEGERI 1 TIMPEH KECAMATAN TIMPEH KABUPATEN DHARMASRAYA - Sus Ria Viningsih (Universitas Negeri Padang, 2013)
The goal of this research are to optain get ficture and knowing the operation of self expantiontrought extracurricular activity in the SekolahMenengahAtasNegeri 1 TimpehKabupatenDharmasraya. This is a descriptive study. The population in this study is all student Sekolah Menengah Atas Negeri 1 Timpeh with amount 208 people. Amount of sampel is 66 people, the technique of Non Probability sampling by using sampling purposive. The instrument of research is questionare, with objective and Likert scale that had tested by validity and reliability. Technique analyse data use percentage formula.The result of the researh shows: enlisted, prepared the equipment, prepared of the advisor, activity and evaluation was well done. So, the operation of self expansion trough extracurricular activity in the Sekolah Menengah Atas Negeri 1 Timpeh Kabupaten Dharmasraya did not good work yet. Kata Kunci: Program pengembangandiri; ekstrakurikuler